Therapy-related B-lymphoblastic leukemia after multiple myeloma. (2022) - Kallen, Michael E.; Koka, Rima; Singh, Zeba N.; Ning, Yi; Kocoglu, Mehmet H.; Badros, Ashraf Z.; Niyongere, Sandrine; Duong, Vu H.; Emadi, Ashkan; Baer, Maria R.
Abstract: New therapies for multiple myeloma have improved outcomes, but are associated with therapy-related hematologic malignancies. We report eight patients with therapy-related B-lymphoblastic leukemias (t-B-ALL) in the setting of therapy for multiple myeloma, which included lenalidomide maintenance. A subset of patients had pancytopenia and low-level marrow involvement by acute leukemia, an unusual finding in de novo B-ALL. One patient died of chemotherapy complications; the other seven responded. No patient died of B-ALL (median follow up of 1.0 years). Our series suggests that t-B-ALL is clonally unrelated to myeloma, presents with diverse cytogenetic abnormalities, and responds well to B-ALL therapy.